Casos y cosas: semanario popular (Vol. 2, No. 45) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Un patan, Alcalde de Iquitos?, Charlas y comentos, Estrellas fugaces, Carta abierta, Apuntes de un ocioso, La penitencia de Juana, Nociones de esgrima

ENGLISH: A lout, Mayor of Iquitos, chats and comments, shooting stars, open letter, notes of an idle man, Juana's penance, fencing notions, etc.
Cases and things: popular weekly (Vol. 2, No. 45)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas